Gender equity in sport from the perspective of European women athletes and sport managers, physical education teachers and sport coaches - Vaquero-Cristóbal, Raquel; Mateo-Orcajada, Adrián; Dağlı Ekmekçi̇, Yeter Aytül; Pereira, Antonino; Amin, Shirin; Meroño, Lourdes; González-Gálvez, Noelia; Ballı, Özgür Mülazımoğlu; Mendes, Francisco; Mbah, Orlando; Abenza-Cano, Lucía; Leiva-Arcas, Alejandro; et al. (Frontiers in Psychology, 2024)
Gender inequality in sport has conditioned women's participation in sport, exposing them to difficult situations and numerous barriers to face. However, no previous research has analysed the situation of women in sport from the perspective of the athletes or from the perspective of the coaches, teachers or managers who work with them. This study examines the perspectives of European women athletes, sports managers, physical education teachers, and sports coaches, on gender equity in sports across six European countries: Greece, Ireland, Italy, Portugal, Spain, and Turkey. The research design was consistent with a critical realist epistemology, and the sampling method was non-probabilistic by convenience. A total of 42 female athletes and 45 sports managers, physical education teachers or coaches, participated in five focus groups in the same countries, in groups of 6 to 10 participants per focus group. Focus groups were conducted to stimulate collective discussions, build upon and question ideas, and reach a consensus on questions drawn up by a group of experts, following previous methodologies. The data analysis involved transcribing, translating, and contextualizing the focus group recordings into English. Inductive thematic analysis, reflexive thematic analysis, and codes and themes within the data were created using NVivo 12 Pro. The results of the study revealed that gender inequality in sports is influenced by the broader social context, where stereotypes, biases, and discrimination persist. The participants also highlighted the challenges, barriers, and needs that women athletes face in their careers, such as a lack of resources, support, visibility, and recognition. Moreover, the participants suggested some strategies to promote gender equity in sports, such as increasing investment, awareness, and education, creating policies and legislation, fostering women’s leadership and role modeling, and developing mixed and inclusive sports projects. According to athletes and sports managers/teachers/coaches, gender inequality is still present in sport. There are barriers and challenges that need to be addressed such as lack of resources, visibility, and recognition for female athletes. Among the strategies that can be used to reverse this situation are increasing investment, awareness, and education, creating policies and legislation, fostering women’s leadership, and developing mixed and inclusive sport projects.